Investigation of a curve using Frenet frame in the lightlike cone - Kulahci, Mihriban (De Gruyter Poland Sp Zoo, 2017)
Often times the language of mathematics is used to formulate physical theories. For example, as in this paper, while Minkowski space or the theory of special relativity were studying, their formulation was given by means of mathematical methods. In this manuscript, we study spacelike normal curves lying entirely in the 2-dimensional and 3-dimensional lightlike cone. In particular, some related theorems and definitions are also given. The study of representations of spacelike normal curves in the lightlike cone has led to the existence of different areas of mathematics and physics.
Keywords: Special relativity; spacetime; spacelike curve; lightlike cone